2016
DOI: 10.4102/hsag.v21i0.1017
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women living with borderline personality disorder

Abstract: Borderline Personality disorder Women a b s t r a c tThere is limited understanding of the experiences of women living with borderline personality disorder. It was therefore decided to discover how women living with this disorder would tell their life story. For the researcher, who worked in a psychotherapy ward where most women were living with borderline personality disorder, the care of these women was of vital importance, as they were less understood by mental health care providers.The research aimed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…In terms of detachment from self, three studies linked chronic emptiness to identity disturbance, reflecting a detachment from sense of self. A qualitative study which asked for the life stories of people with BPD found an emergent theme of chronic feelings of emptiness relating to disturbances in self-identity [101]. This theme included two subthemes-distorted self-image and lack of identity-resulting in chronic emptiness.…”
Section: Dibmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of detachment from self, three studies linked chronic emptiness to identity disturbance, reflecting a detachment from sense of self. A qualitative study which asked for the life stories of people with BPD found an emergent theme of chronic feelings of emptiness relating to disturbances in self-identity [101]. This theme included two subthemes-distorted self-image and lack of identity-resulting in chronic emptiness.…”
Section: Dibmentioning
confidence: 99%
“…Both qualitative and quantitative studies supported chronic feelings of emptiness preceding impulsive behaviours. A qualitative study reported that women with BPD attempt to fill the 'void' they experience by acting impulsively [101], while a longitudinal study found that impulsivity and self-harm mediated the relationship between chronic emptiness and days out of work over time, suggesting that chronic emptiness may underlie and result in behavioural symptoms of impulsivity including self-harm [38]. A study in a sample of college students found that 67% of participants reported feelings of emptiness prior to engaging in self-harm behaviours [85].…”
Section: Dibmentioning
confidence: 99%
See 2 more Smart Citations
“…These models suggest the inability to understand and tolerate internal experiences at times can lead to individuals inhibiting any emotional experience, and an associated feeling of emptiness inside [ 8 , 9 ]. It is hypothesised that people with BPD may engage in maladaptive behaviours to ‘fill up’ the emptiness they experience as distressing [ 10 ] and qualitative accounts of women with BPD highlight the relationship between chronic feelings of emptiness and identity disturbance [ 11 ]. Feelings of chronic emptiness have been associated with aversive experiences and poor outcomes over time.…”
Section: Introductionmentioning
confidence: 99%